Factors Influencing Internet Addiction among Adolescents of Malaysia and Mongolia - Massoud Moslehpour; Uyanga Batjargal (Jurnal Administrasi Bisnis, 2013)
This study was carried out to investigate the factors that might be influencing inter-net addiction among adolescents of Mongolia and Malaysia. The major variables ofthe study were Family Factors, Social Factors and Internet Addiction. The partici-pants were 264 adolescents [123 of whom were Malaysians and 141 of whom wereMongolians]. The study used structured online questionnaire. Internet addiction wasevaluated using IAT (Internet Addiction Test) standardized instrument.Some factors had similar significant influence for both countries, but someshowed opposite outcomes for Mongolian and Malaysia Internet users. Family back-ground had no significant influence on Internet addiction in both countries. On theother hand, online friends, stress and loneliness had positive influences on Internetaddiction in both countries. Entertainment’s showed positive effect on Malaysianpopulation but had no significant influence on Mongolian adolescent. There are sim-ilarities between the Internet users of the two countries; however, users demonstratesome significant differences between the two countries.